Modifikasi Penggunaan Data Hujan Untuk Pemodelan Hidrologi Hujan Aliran Menggunakan Program IFAS - Lilianti Lilianti; Sigit Sutikno; Yohanna Lilis H (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The advancement of technology in remote sensing sector has provided an alternative solution of data availability in hydrological modeling by satellite data appearance. However, the satellite data still has a weaknesses which is probably caused by several factors such as weather condition and the existence of other objects so that data quality is not good. Therefore, the aim of this research is to model the hydrological rainfall-rainoff with three types of rainfall that are satellite rainfall, ground rainfall and modified rainfall using IFAS program in Rokan Sub Watershed, Riau Province. At the verification phase, advanced and backwards simulation will be done respectively in 2005 and 2006 to test the reliability of the model. The result shows that hydrological modeling at calibration phase in 2006 has a better result in satellite rainfall than that of ground and modified rainfall, with coefficient of correlation (R) value 0,574, volume error (VE) 2,985%, and coefficient of efficiency (CE) 0,876.Keywords: rainfall-runoff modeling, satellite rainfall, ground rainfall, modified rainfall, IFAS.